PENGARUH PADAT TEBAR YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BANGGAI CARDINAL FISH (BCF) (Pteropogon kaurdeni) DALAM WADAH TERKONTROL - Ari Andayani; Baiq Hilda Astriana; Nurliah Nurliah (Universitas Mataram, 2018)
Research objective was to determine the effect of different stocking densities on survival and growth of Banggai Cardinal Fish (BCF) (Pteropogon kaurdeni) in controlled containers. The study used an experimental method with a completely randomized design consisting of three treatment densities namely treatment A 0.833 ind / l, treatment B 1.667 ind / l, and treatment C 2.5 ind / l. Each treatment was repeated four times. The result shows that the different stocking densities effect significantly to the survival rate and daily growth rate of BCF, but do not effect significantly to the growth and length gain of BCF. The survival rate of BCF in treatment A gives the highest result (80%) and be followed by treatment B (78%) and treatment C (54%). In addition, the highest daily growth rate of BCF is found in treatment B (0,689%) and this is followed by treatment C (0,614%) and A (0,608% ).